Are Primary and Secondary Provoked Vestibulodynia Two Different Entities? A Comparison of Pain, Psychosocial, and Sexual Characteristics. (1st June 2015) - Aerts, Leen; Bergeron, Sophie; Corsini-Munt, Serena; Steben, Marc; Pâquet, Myriam
Abstract: Introduction: Provoked vestibulodynia (PVD) is suspected to be the most frequent cause of vulvodynia in premenopausal women. Based on the onset of PVD relative to the start of sexual experience, PVD can be divided into primary (PVD1) and secondary PVD (PVD2). Studies comparing these PVD subgroups are inconclusive as to whether differences exist in sexual and psychosocial functioning. Aim: The aim of this study was to compare the pain, sexual and psychosocial functioning of a large clinical and community-based sample of premenopausal women with PVD1 and PVD2. Methods: A total of 269 women (n = 94 PVD1; n = 175 PVD2) completed measures on sociodemographics, pain, sexual, and psychosocial functioning. Main Outcome Measures: Dependent variables were the 0–10 pain numerical rating scale, McGill–Melzack Pain Questionnaire, Female Sexual Function Index, Global Measure of Sexual Satisfaction, Beck Depression Inventory-II, Painful Intercourse Self-Efficacy Scale, Pain Catastrophizing Scale, State-Trait Anxiety Inventory Trait Subscale, Ambivalence over Emotional Expression Questionnaire, Hurlbert Index of Sexual Assertiveness, Experiences in Close Relationships Scale—Revised, and Dyadic Adjustment Scale-Revised. Results: At first sexual relationship, women with PVD2 were significantly younger than women with PVD1 ( P  < 0.01). The average relationship duration was significantly longer in women with PVD2 compared with women with PVD1 ( P  < 0.01). Although women with PVD1 described a significantly longer duration of pain compared with women with PVD2 ( P  < 0.01), no significant subtype differences were found in pain intensity during intercourse. When controlling for the sociodemographics mentioned earlier, no significant differences were found in sexual, psychological, and relational functioning between the PVD subgroups. Nevertheless, on average, both groups were in the clinical range of sexual dysfunction and reported impaired psychological functioning. Conclusions: The findings show that there are no significant differences in the sexual and psychosocial profiles of women with PVD1 and PVD2. Results suggest that similar psychosocial and sex therapy interventions should be offered to both subgroups of PVD.